2015
DOI: 10.11144/javeriana.syp34-67.sese
|View full text |Cite
|
Sign up to set email alerts
|

El smartphone en la educación superior. Un estudio comparativo del uso educativo, social y ubicuo en universidades españolas e hispanoamericanas

Abstract: <p>El objetivo de esta investigación es analizar de forma general y comparada entre cinco universidades españolas y cinco universidades hispanoamericanas el uso educativo, social y ubicuo que los estudiantes universitarios realizan del teléfono inteligente (smartphone). Se analizó una muestra total de 886 estudiantes —442 españoles y 444 hispanoamericanos—. La metodología de investigación consistió en un análisis factorial y en una comparación intergrupos, mediante pruebas paramétricas y no paramétricas.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 16 publications
0
6
0
4
Order By: Relevance
“…The use of smartphones has become a core part of university students' lives. They use smartphones in their academic activity to exchange information, coordinate group work, and consult services [6] and, in their daily life, to communicate, manage information, entertain themselves, play games, etc. [4,7].…”
Section: Literature Reviewmentioning
confidence: 99%
“…The use of smartphones has become a core part of university students' lives. They use smartphones in their academic activity to exchange information, coordinate group work, and consult services [6] and, in their daily life, to communicate, manage information, entertain themselves, play games, etc. [4,7].…”
Section: Literature Reviewmentioning
confidence: 99%
“…It is unquestionable that the use of this device has increased around the world in the last few years, especially in the population within this age range (university students younger than 35). This has extended its use to the area of education, where some studies [16] have shown the student's habits within and outside university spaces, where in the first scenario it is commonly used in transportation and outdoors; while in the second scenario the classrooms, the hallways and the libraries are the most exploited places. It is precisely the attractiveness they possess that has resulted on their use increasing exponentially, with some authors [3,[17][18][19] already speaking about the problematic use of smartphones.…”
Section: Introductionmentioning
confidence: 99%
“…A nivel mundial los usos sociales de los smartphones se orienta, "tanto en España como en Hispanoamérica, hacia actividades relacionadas con el empleo del chat, la mensajería instantánea, el correo electrónico y la interacción en redes sociales [1]. "…”
Section: Marco Teóricounclassified
“…Vazquez-Cano y Sevillano [1] han demostrado que los estudiantes universitarios del mundo hispano hacen un uso intensivo de los dispositivos móviles con fines educativos, tanto dentro como fuera del recinto universitario. Los autores concluyen que estos resultados alientan a estimular a las instituciones, profesores y responsables educativos a mejorar los procesos didácticos del aula universitaria.…”
Section: Marco Teóricounclassified